Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.6 - Factoring Trinomials - Exercise Set: 67

Answer

$(x^2-6)(x^2+1)$

Work Step by Step

The two numbers whose product is $ac= 1(-6)=-6 $ and whose sum is $b= -5 $ are $\{ -6,1 \}$. Using these two numbers to decompose the middle term, then the factored form of the expression, $ x^4-5x^2-6 $, is \begin{array}{l}\require{cancel} x^4-6x^2+x^2-6 \\\\= (x^4-6x^2)+(x^2-6) \\\\= x^2(x^2-6)+(x^2-6) \\\\= (x^2-6)(x^2+1) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.